Synergistic growth suppression of Fusarium oxysporum MLY127 through Dimethachlon Nanoencapsulation and co-application with Bacillus velezensis MLY71 - Lei Yang; Juntao Gao; Dong Xiang; Xinyu Hu; Guan Lin; Yong Liu (Scientific Reports)
Abstract Fusarium oxysporum is a destructive plant pathogen with robust survival mechanisms, complicating control efforts. This study aimed to develop nanoformulated fungicides, screen antagonistic bacteria, and evaluate their combined efficacy. A novel self-emulsifying nanoemulsion (DZW) was formulated using zein and benzaldehyde-modified wheat gluten (BgWG) as carriers for dimethachlon (DTN). The preparation process optimized material ratios and emulsification techniques. Concurrently, antagonistic bacterial strains against F. oxysporum were screened via the plate standoff method, identifying Bacillus velezensis MLY71 as both antagonistic and compatible with DTN. The DZW nanoemulsion achieved a particle size of 93.22 nm, an encapsulation efficiency (EE) of 90.57%, and a DTN loading capacity (LC) of 67.09%, with sustained release over 96 h. The combination of DTN (0.04 mg·mL⁻¹) and B. velezensis MLY71 (1 × 10⁴ CFU·mL⁻¹) achieved a 76.66% inhibition rate against F. oxysporum MLY127, 1.71 times greater than DTN alone, indicating significant synergy. At a DTN concentration of 0.20 mg·mL⁻¹, the combination of DZW and MLY71 showed a synergy coefficient of 1.33. This synergy was also observed in soil environments, indicating its adaptability for controlling soil-borne pathogens. As sustainable management continues to gain attention in agricultural disease control, this study offers a promising strategy for achieving higher efficacy with the same fungicide dose or satisfactory control with reduced fungicide application. The excellent drug-loading performance of BgWG also expanded the applications of the wheat by-product gluten.